Resultados patalógicos, hematológicos e imunológicos da infecção experimental em camundongos Swiss por Angiostrongylus costaricensis - Benvegnú, Elise (2018)
Abdominal angiostrongyliasis (AA) is a zoonosis caused by the nematode Angiostrongylus costaricensis and is considered endemic in the Brazil’s southern region. In order to treat and prevent this pathology, a better understanding of the hostenvironment-parasite triad is needed. Thus, the objective of this work was to analyze the hematological, pathological and cortisol alterations caused by A. costaricensis in mice. The experiment was conducted with infected groups and controls on days 14 (G1) and 24 (G2) post-infection (dpi). In these days, we performed the collection of blood for the hematological exams, serum for the measurement of cytokines and, after the euthanasia of the animals, of organs for the histopathological analysis of each group. We were able to characterize pathological, cortisol and hematological findings of AA in different periods of the A. costaricensis parasite cycle, resulting in characteristic pathological lesions such as eosinophil infiltration in intestinal wall layers, granulomatous reaction and eosinophilic vasculitis, as well as the presence of larvae and nematode eggs in vessels and mucosa of various organs, in both groups. We observed lesions such as granulomas, vasculitis, thrombi, necrosis and inflammation in pancreas, a novelty in this research area. We detected an anemia in the infected G2 group, probably caused by the lesions that the parasite establishes in the host organism. In the leukogram, there was an increase of segmented neutrophils and monocytes, probably caused by the inflammation caused by the nematode. Regarding stress, both groups showed an increase of cortisol in relation to the respective control groups, which could be justified by the parasite disturbance in the host organism, which among other signs causes pain in the affected individuals. By cytokine analysis, we confirmed the inflammation process caused by the nematode, through the increase of interleukin 6 and interferon γ, pro-inflammatory substances and detected a decrease in tumor necrosis factor α, an outcome that may have been influenced by cortisol. We conclude that the animals infected by this nematode develop lesions characteristic of AA, have a normocytic and hypochromic anemia and generate an inflammatory immune response with the participation of INF-γ, TNF-α and IL-6, which can be influenced by cortisol. Also, for the first time such parameters were accessed in Swiss mice up to 24 DPI.